Instrument Test Development Of Mathematics Skill On Elementary School - et al., Sarson W. Dj. Pomalato (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aims of this research are producing the test instrument of mathematics skill on elementary school which is valid and reliable. The instrument test development in this research use the development model of Wilson, Oriondo and Antonio which is modified. The number of testing sample in this research is 160 of students in each class. This research result: 1) the validity index of aiken v is 0.979 in grade IV and 0.988 in grade V. The coefficient of instrument skill in class IV and V are 0.883 and 0.954. The case indicates that the overall item is accepted and reliable to be used for measuring the development of mathematics skill of elementary school students.